Abnormal Function of Circulating Follicular Helper T Cells Leads to Different Manifestations of B Cell Maturation and Differentiation in Patients with Osteosarcoma - Zhao, Gang; Liang, Jianxiao; Cao, Jingjing; Jiang, Shanyong; Lu, Jianshu; Jiang, Baoen (Journal of healthcare engineering, 2022)
Objective. The objective of this study is to investigate the effect of dysfunctional circulating follicular helper T cells (Tfh) on B cell maturation and differentiation in patients with osteosarcoma (OS). Method. Data from 30 OS patients who underwent diagnosis and treatment in our hospital, as well as those of 30 healthy subjects (HC), were collected at the same time. Flow cytometry was employed to identify proportions of CD4+CXCR5+Tfh cells and Tfh cell subtypes Tfh17, Tfh1, and Tfh2 in the patient’s peripheral blood. CD40 L and IFNγ levels were detected after stimulating Tfh cells with an influenza antigen; the positive rates of CD27 and CD38 in B cells were detected before and after coculture with Tfh cells. qRT-PCR was carried out for Blimp-1 expression in B cells, and ELISA was employed to identify the levels of IgM, IgG, and IgA in B cells and IL-2, IL-10, and IL-4 in Tfh cells before and after coculture. Results. The percentage of CD4+CXCR5+Tfh cells in OS patients’ peripheral blood increased significantly. The Tfh cell ratio increased along with the TNM stage, and the Tfh cell ratio in OS metastasis patients is greater than that in nonmetastatic patients. In addition, Tfh2 and Tfh17 cells increased drastically in OS patients, and no meaningful change was seen in Tfh1 cells. CD40 L levels of Tfh cells in OS patients were less than those of the HC group, and IFNγ was substantially increased. After coculturing the OS group’s B cells with Tfh cells, the CD27+ and CD38+ cells of B cells were drastically greater, and Blimp-1 expression was also significantly increased. In addition, the levels of IL-21, IL-4, and IL-10 of Tfh cells in the OS group and the levels of IgA, IgG, and IgM in B cells were significantly reduced after coculture. Conclusion. Dysfunctional Tfh in OS patients can severely inhibit B cell development, maturation, and differentiation.